DFT Study and Synthesis of Novel Bioactive Bispyrazole using Mg/Al-LDH as a Solid Base Catalyst - Akhramez, Soufiane; Achour, Youness; Dib, Mustapha; Bahsis, Lahoucine; Ouchetto, Hajiba; Hafid, Abderrafia; Khouili, Mostafa; El Haddad, Mohammadine (Current Chemical Biology, 2020)
Objective: To synthesize novel bispyrazole heterocyclic molecules may have important biological activities and thus can serve as good candidates for pharmaceutical applications. Methods: The bispyrazole derivatives 3a-m were prepared by the condensation reaction of substituted aromatic aldehydes with 1,3-diketo-N-phenylpyrazole by using Mg/Al-LDH as a heterogeneous catalyst under THF solvent at the refluxing temperature. Results: This protocol describes the synthesis of bioactive compounds under mild reaction conditions, with good yields, and easiness of the catalyst separation from the reaction mixture. Furthermore, a mechanistic study has been performed by using DFT calculations to explain the observed selectivity of the condensation reaction between aryl aldehyde and 1,3- diketo-N-phenylpyrazole via Knoevenagel reaction. The local electrophilicity/ nucleophilicity explains correctly the experimental finding. Conclusion: In summary, the pharmacologically interesting bis-pyrazole derivatives were synthesized through Mg/Al-LDH as a solid base catalyst, in THF as a solvent. The synthesized bioactive compounds containing the pyrazole ring may have important biological activities and thus can serve as good candidates for pharmaceutical applications. Therefore, the catalyst Mg/Al-LDH showed high catalytic activity. Besides, a series of bispyrazole molecules were synthesized with a good yield and easy separation of the catalyst by simple filtration. Moreover, DFT calculations and reactivity indexes were used to explain the selectivity of the condensation reaction between aryl benzaldehyde and 1,3-diketo-N-phenylpyrazole via Knoevenagel reaction, and the results were in good agreement with the experimental finding.
Keywords: global and local reactivity indexes